Analysis, from the perspective “The Theory of Change”, of the challenges and opportunities in the adoption of PMBOK-7 in design and construction projects in the engineering and architecture sector in Costa Rica - Mata-Abdelnour, Erick (2025)
Project management within the Engineering, Architecture, and Construction (EAC) sector in Costa Rica is now facing the new challenge of adopting the PMBOK-7 project management standard, developed by the Project Management Institute (PMI). This article proposes why this challenge could be one of significant dimensions. An analysis of the main differences between the PMBOK-6 and PMBOK-7 standards is presented. Concepts introduced in the new standard, such as the value delivery system, performance domains, and adaptation, are analyzed. Various challenges and opportunities for adoption are proposed. Taking as a starting point an analysis of the public databases of the Federated College of Engineers and Architects (CFIA), a baseline is established for the frequent profiles of the different types of professionals, companies, and projects that are processed through the Construction Project Manager (CPM). This allows for the delimitation of a starting baseline for a potential sector change. The principles of “Theory of Change” and “Adoption of Change” models are used to explain the various stages that could occur in the sector’s transition, and facilitation actions will be proposed for the path of adopting the new standard.